THE ROLE OF MULTIMEDIA IN LEARNING THE FIELD OF CHRISTIAN RELIGION STUDIES ON STUDENT LEARNING CREATIVITY DURING THE COVID-19 PANDEMIC - Bangun Munte; Nurliani Siregar; Imelda Butarbutar; Bangun; Jojor Silalahi; Janwar Tambunan (Jurnal Scientia, 2022)
The purpose of this study was to see how far the Role of Multimedia in Learning in the Field of Christian Religion Studyed on Student Creativity During the Covid-19 Pandemic. The number of samples is 38 people. This study uses a descriptive method, while the data analysis carried out in the hypothesis research is Pearson's product moment correlation with the data collection tool is a questionnaire for Variable X (The Role of Multimedia in Learning the Field of Christian Studies) and Variable Y (Student Learning Creativity). To find out the extent of the Role of Multimedia in Learning the Field of Christian Religion Studies on Student Creativity During the Covid-19 Pandemic, the Pearson Product Moment Correlation Statistics test. From the test results, it was obtained that the correlation (r) was 0.36 with a determination test of 12, then a "t" test is held with the test criteria if the t count obtained from the calculation is greater (>) than ttable at a significant level of I 0.05 with dk = n - 2 then the hypothesis is accepted and in other cases rejected. From the test results obtained tcount > ttable (2.30 > 1.69), then the hypothesis is accepted. Thus, it can be stated that there is a meaningful role between the role ofMultimedia in Learning the Field of Study of Christianity Against Student Creativity During the Covid-19 Pandemic.